Multitasking and Job Satisfaction amongst Secondary School Teachers at the District of Klang, Selangor Malaysia - Jamian, Leele Susana; Mohd Nazir, Mohd Syarudin; Gurnam, Kaur Sidhu; Othman, Khairunnisa; Saidin, Norshiha (UiTM Press, 2020)
The role of a teacher has always been challenging especially in the 21st century. Ranging from teaching, extra-curricular activities, sports, administrative, to non-academic matters, teachers teaching in the secondary schools tend to multitask their daily duties. Added with numerous responsibilities in the digital era, doing just one thing at a time seems to be very luxury yet awfully wasteful. Indeed, multitasking was considered essential in today’s work efficiency. Based on observation and empirical studies, multitasking tends to influence and contribute to teachers’ job satisfaction. Nonetheless, there are also gaps in the existing local literature pertaining to multitasking and job satisfaction amongst teachers in the Malaysian local school context. In view of this, the current study is conducted with the primary aim to investigate the relationship between multitasking and job satisfaction amongst the secondary school teachers in one of the districts of Klang, Selangor, Malaysia. A descriptive correlational research design using a mixed-methods approach was employed to explore the relationship between the two variables. Two instruments measuring multitasking by Woods, Boyd, Rand, Nardo and Boyd (2014) and Job Satisfaction survey by Spector (1997) were adapted to suit the local setting for data responded by 124 secondary school teachers. The quantitative findings revealed that there were significant, positive and moderate relationships between multitasking and job satisfaction. However, findings from the multiple regression indicated that only 11.3% of the variance in job satisfaction was contributed by multitasking. In addition, qualitative data tend to triangulate the quantitative findings. Besides positive responses, there were also voices that proposed otherwise. Consequently, all these findings lead to some important implications in terms of the corpus of knowledge and policy implication related to the two variables of educational management and leadership amongst the teachers cum instructional leaders in the academic setting.